Depression in Harry’S Moments Prior to Death in Ernest Hemingway’s Short Story The Snows of Kilimanjaro - Jumino Jumino (Sabda: Jurnal Kajian Kebudayaan, 2026)
AbstractThis article analyzes the depiction of depression prior to death experienced by Harry, the main character in Ernest Hemingway’s short story The Snows of Kilimanjaro. This study aimed to examine how Harry’s thoughts and behaviors reflect his depression as he approaches death. This study used a qualitative descriptive method with a psychological approach. The analysis applies Aaron T. Beck’s cognitive triad as the main theory, supported by depressive symptoms such as self-criticism, guilty feelings, use of humor, absolutistic thinking, viewing problems as overwhelming, passivity, and avoidance. The results show that Harry evaluates himself as a failed writer, interprets his past as a series of mistakes, and sees no possibility of changing his future. These negative thoughts influenced his behavior, which was reflected in his refusal to move, doubts about medical treatment, and acceptance of death. This article shows that depression affects both thought patterns and behavior prior to death.